2011
DOI: 10.1007/s00417-011-1771-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical low-coherence reflectometry enables preoperative detection of zonular weakness in pseudoexfoliation syndrome

Abstract: The optical low-coherence reflectometry enabled preoperative detection of zonular weakness and subsequent lens instability documented as a significantly shallower anterior chamber, thicker lens, and smaller pupillary diameter in the pseudoexfoliation syndrome group in the studied population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
12
0
3
Order By: Relevance
“…Some studies found significantly shallower anterior chambers in eyes with PEX compared to age- and gender-matched patients without PEX syndrome and primary open-angle glaucoma. 7,8,23,24 Bosnar et al 7 compared the optical ocular features of 47 eyes with cataract complicated by PEX syndrome with 177 eyes with uncomplicated cataract using the Lenstar LS 900® OLCR instrument. ACD was lower (t=-2.24, p<0.05) and LT (t=3.01, p<0.001) was higher in the PEX group (2.43±0.38, 4.70±0.39, respectively) compared to the control group (2.59±0.45, 4.43±0.57, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found significantly shallower anterior chambers in eyes with PEX compared to age- and gender-matched patients without PEX syndrome and primary open-angle glaucoma. 7,8,23,24 Bosnar et al 7 compared the optical ocular features of 47 eyes with cataract complicated by PEX syndrome with 177 eyes with uncomplicated cataract using the Lenstar LS 900® OLCR instrument. ACD was lower (t=-2.24, p<0.05) and LT (t=3.01, p<0.001) was higher in the PEX group (2.43±0.38, 4.70±0.39, respectively) compared to the control group (2.59±0.45, 4.43±0.57, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,4,5 Zonular instability may lead to intraoperative complications during cataract surgery, most notably zonular dialysis and vitreous loss. 3,4,5,6,7,8 Previous studies showed that zonular weakness with subsequent phacodonesis in PEX syndrome could lead to anterior lens movement, increased lens thickness (LT) and shallow anterior chamber. 6,7,8 In eyes with PEX syndrome, a small anterior chamber depth (ACD) less than 2.5 mm was found to be associated with a risk of 13.4% for intraoperative complications compared with an incidence of 2.8% for an ACD of 2.5 mm or more.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that the insufficient suspension apparatus of the lens and decentralization of the entire capsular bag are the main reasons for IOL decentralization in patients with PEX. 18 Bosnar et al 19 proposed that optical low-coherence reflectometry may be used preoperatively in eyes with PEX to detect the zonular weakness and subsequent lens instability, which documented as significantly shallower anterior chamber, thicker lens, and smaller pupillary diameter. Kuchle et al observed an earlier and significantly higher frequency of secondary cataract in eyes with PEX after extracapsular cataract extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent uncomplicated phacoemulsification surgery with a hydrophobic square-edged posterior-chamber IOL (Alcon IQ, Fort Worth, TX) at least six months before posterior capsulotomy and who experienced PCO that deteriorated visual acuity were included in the study. The mean time between posterior capsulotomy and cataract surgery was 17.2366.8 months (range: 8-35 months) and 19.2367.1 months (range: 6-32 months) in group 1 and 2, respectively.…”
Section: Methodsmentioning
confidence: 97%